PP21 Informing intervention design to improve diet and physical activity during pregnancy: a qualitative study of the attitudes and experiences of women and healthcare providers. (31st August 2015) - McHugh, SM; Flannery, C; Clifford, E; Kenny, L; Kearney, PM
Abstract : Background: Overweight and obesity during pregnancy is associated with an increased risk of gestational diabetes mellitus (GDM), preeclampsia and macrosomia among other complications. Antenatal lifestyle interventions have been shown to be effective in this population however studies often fail to identify the mechanisms by which the intervention is expected to be effective. Our aim is to identify the barriers and enablers to behaviour change from the perspective of obese pregnant women and their healthcare providers (HCP), with a view to informing a lifestyle intervention to reduce the risk of GDM. Methods: Semi-structured interviews are being conducted with a purposive sample of doctors and midwives recruited from a large academic maternity hospital in the Republic of Ireland (n = 1–15). A purposive sample of obese women at different stages of pregnancy will also be recruited from public and private antenatal clinics (nn = 1–15). The Framework approach is being used during analysis, drawing on the Theoretical Domains Framework (TDF). The TDF identifies 12 domains which can act as barriers or facilitators to behaviour change. Results: Preliminary analysis of HCP interviews suggests that pregnancy is 'a wake-up call' for some women as the risks of obesity are made explicit. Social influences were identified as a potential facilitator; HCP suggested behaviour change was easier for pregnant women when supported by their partners or when partners also engaged in healthy lifestyle behaviours. Healthcare professionals identified the environmental context and resources as barriers, particularly the lack of dedicated obesity clinics and the limited access to dietetic services. Discussion: Healthcare professionals believe pregnancy offers a window of opportunity to engage women in behaviour change as beliefs about consequences of overweight and obesity for the baby may trigger behaviour change in the pregnant woman. However, there are limited resources available to them to support women to make health behaviour changes.